Managing nano-bio-info-cogno innovations - BAINBRIDGE, WILLIAM SIMS.; ROCO, MIHAIL C.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Tremendous human progress is becoming possible through the development of converging technologies stimulated by advances in four core fields: Nanotechnology, Biotechnology Information technology, and new technologies based in Cognitive science (NBIC). This book provides a unique review of technical developments related to the unification that is rapidly taking place today among these fields. It assesses potential for revolutionary applications of these developments and their likely impact in improving the human condition. The essays included in the book offer a wide variety of scholarly views on the likely societal impacts and policy implications of these developments and applications, including assessments of educational, economic, commercial, legal, ethical, political, and social implications. This is the third in a series of such volumes on converging technologies edited by Drs. Roco and Bainbridge, the first of which is also available from Springer.
Progressive Convergence -- The Emergence and Policy Implications of Converging New Technologies -- Roadmapping Convergence -- NBIC Convergent Technologies and the Innovation Economy: Challenges and Opportunities for the 21st Century -- Measuring the Merger: Examining the Onset of Converging Technologies -- Collaboration on Converging Technologies: Education and Practice -- If We Build It, Will They Come? The Cultural Challenges of Cyberinfrastructure Development -- Converging Technologies in Developing Countries: Passionate Voices, Fruitful Actions -- Nanotechnology for Biology and Medicine -- Biologically-Inspired Cellular Machine Architectures -- Cognitive Enhancement and the Neuroethics of Memory Drugs -- Neuropolicy (2005 2035): Converging Technologies Enable Neurotechnology, Creating New Ethical Dilemmas -- Information Technology and Cognitive Systems -- Cognitive Technologies -- NBIC Convergence and Technology-Business Coevolution: Towards a Services Science to Increase Productive Capacity -- An Ethic for Enhancing Human Performance Through Integrative Technologies -- Science Confronts the Law -- Human Enhancement and the Emergent Technopolitics of the 21st Century -- Co volution of Social Science and Emerging Technologies.
Keywords: CHEMISTRY; NEUROSCIENCES; BIOTECHNOLOGY; BIOMEDICAL ENGINEERING; ECONOMICS; TECHNOLOGY; NANOTECHNOLOGY; CHEMISTRY; NANOTECHNOLOGY; BIOTECHNOLOGY; R & D/TECHNOLOGY POLICY; TECHNOLOGY MANAGEMENT; BIOMEDICAL ENGINEERING; NEUROSCIENCES